Machine learning for liquidity risk modelling: A supervisory perspective - Guerra, Pedro (2022)
Guerra, P., Castelli, M., & Côrte-real, N. (2022). Machine learning for liquidity risk modelling: A supervisory perspective. Economic Analysis and Policy, 74(June), 175-187. https://doi.org/10.1016/j.eap.2022.02.001